Diagnosis of CO2 dynamics and fluxes in global coastal oceans. Issue 4 (2nd August 2019) - Cao, Zhimian; Yang, Wei; Zhao, Yangyang; Guo, Xianghui; Yin, Zhiqiang; Du, Chuanjun; Zhao, Huade; Dai, Minhan
Abstract: Global coastal oceans as a whole represent an important carbon sink but, due to high spatial–temporal variability, a mechanistic conceptualization of the coastal carbon cycle is still under development, hindering the modelling and inclusion of coastal carbon in Earth System Models. Although temperature is considered an important control of sea surface p CO2, we show that the latitudinal distribution of global coastal surface p CO2 does not match that of temperature, and its inter-seasonal changes are substantially regulated by non-thermal factors such as water mass mixing and net primary production. These processes operate in both ocean-dominated and river-dominated margins, with carbon and nutrients sourced from the open ocean and land, respectively. These can be conceptualized by a semi-analytical framework that assesses the consumption of dissolved inorganic carbon relative to nutrients, to determine how a coastal system is a CO2 source or sink. The framework also finds utility in accounting for additional nutrients in organic forms and testing hypotheses such as using Redfield stoichiometry, and is therefore an essential step toward comprehensively understanding and modelling the role of the coastal ocean in the global carbon cycle.